Developing Connectedness to Nature in Urban Outdoor Settings: A Potential Pathway Through Awe, Solitude, and Leisure - Mateer, Timothy J. (Frontiers in Psychology, 2022)
Outdoor leisure experiences may represent an understudied yet effective pathway to promote connectedness to nature for urban park visitors. In contrast to outdoor recreation, this critical essay argues outdoor leisure more heavily emphasizes eudaimonic sentiments and intrinsic motivation in comparison to the goal-oriented and hedonic nature of outdoor recreation. It is further argued that two specific social psychological constructs, awe and solitude, may be especially useful in promoting leisure experiences in urban outdoor spaces. Relevant philosophical and social psychological literature is reviewed and synthesized to outline how land managers and environmental educators may facilitate experiences of awe and solitude to better promote contexts for experiencing outdoor leisure in urban parks. Specifically, reviewed literature suggests that utilizing the recreation opportunity spectrum framework and co-creative processes may be an effective path forward in better supporting urban park environments that are conducive to awe, solitude, and leisure. The review and synthesis of this research may ultimately guide environmental educators, land managers, and researchers in ways to more effectively support connectedness to nature via outdoor leisure experiences as an outcome for visitors to outdoor urban spaces.